The Meaning of Life in the Thought of Al-Gazālī and Viktor Frankl: A Comparative Study of Spiritual and Psychological Approaches to Authentic Happiness - Muhamad Zaenal Arifin (KURAS Institute, 2025)
This research seeks to analyze the concept of happiness through the lenses of al-Gazālī's Sufism and Viktor Frankl's logotherapy. Utilizing a qualitative approach, the study employs library research to gather data from various primary and secondary sources, including al-Gazālī's Iḥyā’ ‘Ulūm al-Dīn and Frankl's Man's Search for Meaning. The analysis is conducted through a descriptive-analytical method, exploring the similarities and differences between these two frameworks in their interpretations of the search for meaning in life as a pathway to happiness. The findings demonstrate that both al-Gazālī's Sufism and Frankl's logotherapy argue that happiness is not solely reliant on material conditions; instead, it is intricately linked to the meaningfulness of life, which can be discovered through worship, personal experiences, creativity, and the attitudes we adopt when confronting challenges. Al-Gazālī asserts that true happiness can be attained through a spiritual approach that involves drawing closer to God, while Frankl posits that individuals possess the freedom to find meaning in their lives. This study proposes a holistic transformative model that bridges the spiritual and psychological aspects of the search for life's meaning by integrating these two approaches. This research makes both theoretical and practical contributions in understanding and leveraging the concept of life's meaning to attain genuine happiness.